Risk Situation of Bromate Contained in Bottled Drinking Water and Natural Mineral Water Distributed in Thailand - จิตติยศรา, กรรณิกา; สิงศาลาแสง, สาคร; พรหมหิรัญกุล, ประภาพรรณ; แร่กาสินธุ์, นิรันดร; สาขะจร, สุจิตร; ชะพลพรรค, พรรคพล; เอี่ยมบู่, สุวิมล (Journal of Health Science of Thailand, 2020)
Bromate is mutagenic possibly carcinogenic to humans. It can be found in drinking water as a by-product from water disinfected by ozone. No regulatory limit has been established in Thailand. This study aimed to evaluate risk situation from intake of bromate in bottled drinking water and natural mineral water distributed in Thailand in 2014 and a follow-up assessment in 2019. For the year 2014, the total of 566 samples from 60 provinces in Thailand with trademark was consisted of 511 samples of ozone treated bottled drinking water treatment system, 55 samples of natural mineral water, 24 samples were locally produced and 31 samples were imported. The 2019 study, there were 67 samples collected from 12 provinces including 4 imported samples. The analysis was performed using ion chromatographic technique with LOD and LOQ of 1 and 3 µg/L respectively, recovery of 99-112% and relative standard deviation (RSD) of 2.4-8.4%. The results showed that 10.0% of bottled drinking water collected in 2014 contained bromate in the range of <3-177 µg/L; and 18.2% of mineral water contained bromate in the range of <3-134 µg/L. Similar investigation conducted in 2016 revealed that bromate was still found in 9.8% of the drinking water samples with the range of 5.7-41.0 µg/L, and 60% in natural mineral water with the range of <3-68.5 µg/L. The health risk assessment revealed the hazard quotient (HQ) of less than 1. However, the excess cancer risks (ECR) in both bottled drinking water and mineral water was over 2x10-5, the acceptable risk level set by the World Health Organization. Therefore, the national authority should establish a regulatory limit for bromate in drinking water in Thailand in order to protect the consumers.